Políticas sociais e hegemonia: um estudo sobre o processo de formulação da proposta de reforma sanitária - Grynszpan, Walter (2005)
The principles of the Unified Health System (Sistema Único de Saúde - SUS) - universal attendance, integrated and decentralized administration and the users' participation - were included in the Federal Constitution of 1988 as a result of a political movement around the subject of the health which has begun in the second half of the decade of 70, together with the overcoming process of the authoritarian regimen established in 1964. This movement, which got the name of sanitary movement or movement for the Sanitary Reform, can be understood in its relationship with a process of cultural changing among the Brazilian left, that looked for new forms of facing the democracy and, with it, the social policy. This work part of the premise that one of the main influences to guide this new vision was the Italian Marxist Antonio Gramsci's thought. We've tried to identify, in the formation of the speech on the Sanitary Reform and in the definition of the political strategies of those that make efforts for it, the influences of Gramsci. To reach this objective, we analyzed the editorials of Saúde em Debate (Health in Debate) magazine, official vehicle of the Centro Brasileiro de Estudos de Saúde (Brazilian Health Studies Center - Cebes), which is still in activity, that represented, in the analyzed period, 1976 to 1988, the critical thought about the reality of the health in the country and finished to be the institution that supported the project of Sanitary Reform.